1997
DOI: 10.1002/(sici)1097-0215(19971210)73:6<880::aid-ijc20>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspirin on cell proliferation and differentiation of colon adenocarcinoma Caco‐2 cells

Abstract: Several lines of evidence suggest that long-term treatment with non-steroidal anti-inflammatory drugs may reduce the risk of colon cancer and the size and number of colonic polyps in patients with familial adenomatous polyposis. Aspirin has also been shown to inhibit cell proliferation in human tumor cell lines and to induce apoptosis in colonic mucosa of familial polyposis patients. To elucidate the molecular mechanisms of the antiproliferative action of aspirin, we studied the effects of aspirin on cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
11
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
5
11
0
Order By: Relevance
“…However, we found that in B-CLL cells aspirin induces all the typical features of apoptosis, including internucleosomal DNA fragmentation, decrease in DNA content, increase in phosphatidylserine exposure and proteolysis of poly(ADPribose) polymerase (PARP) (Bellosillo et al, 1998). Consistent with our results, it has been reported that aspirin induces apoptosis of colon adenocarcinoma Caco-2 cells (Ricchi et al, 1997), HT-29 cells (Qiao et al, 1998) and crypt cells (Barnes et al, 1998). The apoptotic action of aspirin on B-CLL cells was inhibited by the caspase inhibitor Z-VAD.fmk, demonstrating the involvement of caspases (Bellosillo et al, 1998).…”
supporting
confidence: 92%
“…However, we found that in B-CLL cells aspirin induces all the typical features of apoptosis, including internucleosomal DNA fragmentation, decrease in DNA content, increase in phosphatidylserine exposure and proteolysis of poly(ADPribose) polymerase (PARP) (Bellosillo et al, 1998). Consistent with our results, it has been reported that aspirin induces apoptosis of colon adenocarcinoma Caco-2 cells (Ricchi et al, 1997), HT-29 cells (Qiao et al, 1998) and crypt cells (Barnes et al, 1998). The apoptotic action of aspirin on B-CLL cells was inhibited by the caspase inhibitor Z-VAD.fmk, demonstrating the involvement of caspases (Bellosillo et al, 1998).…”
supporting
confidence: 92%
“…The inhibition of growth was associated with a reduction in IGF-II mRNA expression and with the induction of the enterocyte-like di erentiation of the cells (Ricchi et al, 1997). This ®nding suggested that aspirin by reducing IGF-II expression in turn downregulated cyclo-oxygenase activity and increased apoptosis in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 91%
“…Aspirin treatment inhibits proliferation of Caco-2 cells and induces the enterocyte-like di erentiation of the cells before they reach con¯uency. These e ects are associated with a dose-dependent reduction in IGF-II mRNA expression (Ricchi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that nonselective and COX-2-selective inhibitors are able to inhibit cell growth and induce apoptosis in colon cancer cells (Elder et al, 1997;Ricchi et al, 1997;Di Popolo et al, 2000).…”
Section: Common Death Pathways Between Nsaids and Anticancer Drugsmentioning
confidence: 97%